Earthquake design practice for buildings - Booth, E. D. (ICE Publishing, 2020)
'Earthquake Design Practice for Buildings' is an internationally applicable, practical guide for engineers to the seismic design of buildings for earthquake-resilient communities. This edition continues to provide comprehensive, practical, easy to read advice on the technical issues that have to be considered in the seismic design of buildings.